2022
DOI: 10.3390/nu14040839
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Concentration during Early Pregnancy as an Accurate Predictor of Anemia during Late Pregnancy

Abstract: It is undetermined which blood variables related to iron storage during the first trimester of pregnancy could efficiently predict anemia occurring during the third trimester. Red blood cell count (RBC), hemoglobin concentration, hematocrit, ferritin, iron, and total iron binding capacity (TIBC) were assessed longitudinally during the first, second, and third trimesters of 231 healthy Japanese women. None of the patients had anemia in the first trimester and none used iron supplementation before the second tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
4
0
2
Order By: Relevance
“…The prevalence of anemia increased dramatically during pregnancy to reach 21.9% at T3 despite iron supplementation at T1 of all women with IDA at T1. These results were expected in High-Income Countries [ 2 , 14 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The prevalence of anemia increased dramatically during pregnancy to reach 21.9% at T3 despite iron supplementation at T1 of all women with IDA at T1. These results were expected in High-Income Countries [ 2 , 14 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 71%
“…Transferrin saturation (TfS) was not performed because we determined SF, which demonstrated better efficacy for diagnosing IDA in pregnancy [ 6 , 20 ]. Furthermore, the study of Noshiro et al [ 14 ] demonstrated that the sensitivity of TfS is only 17% in predicting anemia in the third trimester, which validated our choice a posteriori. We decided to devote the budget of the study to more original and less studied parameters, Hepc and STfR, with the calculation of the SF/STfR ratio.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Blood is collected from a vein or capillary to test for hemoglobin, which can be inconvenient and painful and increase the risk of infection. Most anemic patients are pregnant women, children, or those recovering from major surgeries, as well as those with severe chronic diseases, who are immunocompromised, or who have coagulation disorders [ 3 , 4 , 5 , 6 ]. Frequent blood tests can also lead to poor compliance.…”
Section: Introductionmentioning
confidence: 99%